Comparison of microwave dielectric properties of human normal, benign and malignant thyroid tissues obtained from surgeries: a preliminary study. (14th May 2018) - Gavazzi, Soraya; Limone, Paolo; De Rosa, Giovanni; Molinari, Filippo; Vecchi, Giuseppe
Abstract: The aim of this work was to investigate whether there are differences in electromagnetic properties between normal and variously pathological human thyroid tissues. Dielectric properties of normal, diseased and malignant human thyroid tissues have been investigated at microwave frequencies from 200 MHz to 10 GHz; diseased tissues involved goiters, thyroiditis and adenomatous nodules. Measurements were carried out on freshly excised thyroid samples from 14 surgery patients within less than one hour from excision, using the open-ended coaxial probe technique. Complex permittivity values of each measured specimen were fitted to a 2-pole Cole–Cole model. Thyroid samples were classified into five categories according to their final histological examination: normal, struma (nodular goiter), thyroiditis, adenoma and cancer. Data analysis showed that the dielectric constant of a normal thyroid is on average 10% lower than relative permittivity of cancer and less than 8% lower than that of goiter over the entire frequency band. Conductivity for normal samples is from 21% to 8% lower than that for malignant lesions and from 14% to 7% lower than conductivity of goiter (struma) in the band ranging from 0.2 to 2.45 GHz. Above this frequency range no significant difference is found in terms of electrical conductivity. No significant contrast has, however, been found between dielectric properties of cancer and other benign pathologies affecting the gland. These findings are relevant for microwave diagnosis endeavours and for all biomedical applications involving the electrical properties of human tissues.